2019
DOI: 10.1002/ags3.12286
|View full text |Cite
|
Sign up to set email alerts
|

Verification of inflammation‐based prognostic marker as a prognostic indicator in hepatocellular carcinoma

Abstract: AimAlthough inflammation‐based markers in cancer have been used for prognostic prediction, the most useful marker for hepatocellular carcinoma (HCC) has not been established. We investigated the usefulness of various inflammation‐based markers in HCC patients after hepatectomy.MethodsA total of 478 patients who underwent initial hepatectomy for HCC from 2009 to 2015 and were diagnosed with pathological HCC were included in this retrospective study. Inflammation‐based markers consisted of the C‐reactive protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…[4][5][6] There is increasing evidence that correlates preoperative immunological statuses with not only postoperative complications but also long-term outcomes of patients with certain tumors, which is associated with poorer cancer-specific survival in patients with malignant tumors. [7][8][9] In addition, a growing number of studies have shown that circulating immune inflammatory cells such as platelets, neutrophils and lymphocytes play an important role in promoting the proliferation, invasion and migration of cancer cells by changing the tumor microenvironment. 10 Recently, several inflammation-based scores, mainly including SII, NLR and PLR, have been served as useful prognostic biomarkers for multiple solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] There is increasing evidence that correlates preoperative immunological statuses with not only postoperative complications but also long-term outcomes of patients with certain tumors, which is associated with poorer cancer-specific survival in patients with malignant tumors. [7][8][9] In addition, a growing number of studies have shown that circulating immune inflammatory cells such as platelets, neutrophils and lymphocytes play an important role in promoting the proliferation, invasion and migration of cancer cells by changing the tumor microenvironment. 10 Recently, several inflammation-based scores, mainly including SII, NLR and PLR, have been served as useful prognostic biomarkers for multiple solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, some studies have shown that inflammation factors are associated with prognosis in patients with cancer [ 16 18 ]. SII is widely accepted to be a new predictive marker to predict the prognosis of several types of cancer [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, both local (CRP) and systemic (ESR) has recently emerged as an important reflection of HCC aggressiveness and prognosticator. Various other clinical approaches have been taken to its measurement, including peripheral blood neutrophil to lymphocyte (NLR) and platelet to lymphocyte (PLR) ratios 21,33‐49 . These novel markers of disease activity are especially needed for that 50% of HCC patients who do not have elevated AFP levels 30,46,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Various other clinical approaches have been taken to its measurement, including peripheral blood neutrophil to lymphocyte (NLR) and platelet to lymphocyte (PLR) ratios. 21,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] These novel markers of disease activity are especially needed for that 50% of HCC patients who do not have elevated AFP levels. 30,46,50 However, a central unanswered question is why elevated values of these inflammation markers predict poor survival.…”
Section: Discussionmentioning
confidence: 99%